Insan Sejahtera Modules as the Foundation for Comprehensive Excellence - Mohd Basri, Mohd Rafaie; Taib, Taifunisyam; Saidin, Norhafizah; Abdullah, Shamsuddin; Ibrahim, Zainul Abidin; Wan Abdullah, Wan Radziah; Aling, Noor Asiah; Ismail, Nur Farrah Syazwanie; Ahmad, Salina; Md Zahir, Mohd Syauqi (Centre of Foundation Studies, Universiti Teknologi MARA, Cawangan Selangor, Kampus Dengkil, 2022)
The International Islamic University Malaysia have formulated a comprehensive framework for education called Sejahtera Academic Framework (SAF) in its effort to humanise education. Insan Sejahtera, as the ultimate end of the framework, is a manifestation of a well-balanced individuals integrated with good faith, knowledge and good character for sustainable development of Malaysia, Muslim ummah and global population. At the Centre for Foundation Studies, the concept of Insan Sejahtera is formally introduced to the students during their orientation programme. The Insan Sejahtera modules, which focus on the concepts of KhAIR, are set to expose the students on the Sejahtera Academic Framework (SAF) of the university and serve as an alignment tool to shift their paradigm to a comprehensive framework of IIUM. Arguably the first integrated modules for orientation, the modules are tailored to the aspiration of IIUM, making the modules as a part of the continuous processes in nurturing an Insan Sejahtera. Being adaptable and universal, the modules can be eveloped further as a model for implementation in all institutions. By that, a mutual understanding between the students and institution can be established earlier on and eventually will serve as a common platform for the humanising education processes.